Gender differences in occupational injury incidence. Issue 3 (14th January 2015) - Berecki‐Gisolf, Janneke; Smith, Peter M.; Collie, Alex; McClure, Roderick J.
<x xml:space="preserve">Abstract</x> Objectives To describe the frequency and distribution of workplace injury claims by gender, and quantify the extent to which observed gender differences in injury claim rates are attributable to differential exposure to work‐related factors. Methods WorkSafe Victoria (Australia) workers' compensation data (254, 704 claims with affliction onset 2004–2011) were analysed. Claim rates were calculated by combining compensation data with state‐wide employment data. Results Mental disorder claim rates were 1.9 times higher among women; physical injury claim rates were 1.4 times higher among men. Adjusting for occupational group reversed the gender difference in musculoskeletal and tendon injury claim rates, i.e., these were more common in women than men after adjusting for occupational exposure. Conclusions Men had higher rates of physical injury claims than women, but this was mostly attributable to occupational factors. Women had higher rates of mental disorder claims than men; this was not fully explained by industry or occupation. Am. J. Ind. Med. 58:299–307, 2015. © 2015 Wiley Periodicals, Inc.